Risk Management for 4-H Youth Development Work: Pre-Event Planning Guide and Matrix - Dale Pracht; Marilyn Norman; Kate Fogarty; Jean Hink (EDIS, 2010)
4H10.8, a 3-page fact sheet by Dale Pracht, Marilyn Norman, Kate Fogarty, and Jean Hink, is part of the Risk Management for 4-H Youth Development Work series. It outlines the steps to use the pre-event planning matrix, which helps leaders prepare for activities that involve risk. Includes references. Published by the Florida 4-H Youth Development Program, August 2010.